Jurnal BUSINESS & ENTREPRENEURSHIP: the evaluation on the financial performance of paper and pulp companies in Indonesia - Rinaldi syahran, Dedi budiman hakim; dadang sukandar (SB-IPB, 2016)
pada tahun 2013 pemerintah menjadikan industri pulp dan kertas sebagai sektor strategis